Using classcraft to develop students conceptual understanding and motivation to learn - Furio, Glenah A.; Que, Elenita N.; Abesamis, Gerson M.; Olegario, Lizamarie Campoamor; Yangco, Rosanelia Timtiman; Maligalig, John Paul F. (Quezon City College of Education, University of the Philippines Diliman, 2019)
The Philippine educational system has continually responded to the call of honing and equipping Filipino students to be globally competitive. Technology has played a vital role in assisting education practitioners in developing local students in terms of conceptual understanding to enable them to utilize their skills in real-life context. Motivating students is always viewed as a challenging task among teachers for learners that vary from one generation to another. In learning science concepts, it is a must to address students conceptual understanding and this is made possible through an appropriate motivation. Gamification is believed to pave the way in its quest to integrate technology in improving students conceptual understanding and further motivating them in learning science concepts. This study aimed to determine the effects of Gamification on students conceptual understanding and motivation in learning among Grade 7 students in a Junior High School in Valenzuela City. Specifically, it sought to answer the following research questions: (1) Do students exposed to gamification have better conceptual understanding than those exposed to conventional teaching? (2) Do students exposed to gamification have higher levels of motivation than those exposed to conventional teaching? (3) Which gamification elements affect students motivation and how do these elements affect students motivation? The study utilized quasi-experimental two group pretest-posttest design involving two heterogeneous groups. The participants were composed of 34 Grade 7 students from biology class in a Junior High School in Valenzuela City. For the biology class, students were split into two groups: one group was taught with Conventional Teaching Approach (ConTA) (comparison group) and the other group was taught using Gamified Biology Teaching Approach (GBTA) (experimental group). The pre-and post-tests using Biology Conceptual Understanding (BCUT) were conducted and recorded for both groups. The results of this study show that ConTA students who were exposed to the conventional methods have better conceptual understanding than the GBTA students who were taught via gamification methods. The level of motivation of the selected students was addressed using Intrinsic Motivation Inventory (IMI). The results show that the students the overall level of motivation of the students in the GBTA group is higher than the ConTA group. Game Element Inventory (GEI) utilized linear regression to identify which game element significantly affect students motivation to learn and the results show that among the seven gamification elements, point and teammates effectively impact the motivation of the students. Focus Group Discussion (FGD) was used to support the data analysis. In light of the results of the study, it is recommended that the students represented by the student community seek help with the teachers, educators and the school administration to initiate, and implement gamification. Further research is also recommended to the Educational Technology and Instructional Designers to develop a gamified learning content which contains systematic methodology for instructional design.
Thesis
Includes bibliographical references.
Keywords: Gamification; Educational technology -- Philippines -- Valenzuela City; Motivation in education -- Philippines -- Valenzuela City; Biology -- Study and teaching (Secondary) -- Philippines -- Valenzuela City; Intrinsic motivation inventory -- Philippines -- Valenzuela City; Game element inventory; Focus group discussion